Application of Optimized and Validated Agar Overlay TLC–Bioautography Assay for Detecting the Antimicrobial Metabolites of Pharmaceutical Interest. (7th August 2020) - Nuthan, Bettadapura Rameshgowda; Rakshith, Devaraju; Marulasiddaswamy, Kuppuru Mallikarjunaiah; Rao, H C Yashavantha; Ramesha, Kolathur Puttamadaiah; Mohana, Nagabhushana Chandra; Siddappa, Shiva; Darshan, Doreraj; Kumara, Kigga Kaadappa Sampath; Satish, Sreedharamurthy
Abstract: The agar overlay TLC–bioautography is one of the crucial methods for simultaneous in situ detection and separation of antimicrobial metabolites of pharmaceutical interest. The main focus of this research relies on the dereplication of an antimicrobial metabolite coriloxin derived from mycoendophytic Xylaria sp. NBRTSB-20 with a validation of agar overlay TLC–bioautography technique. This polyketide metabolite coriloxin was purified by column chromatography, and its purity was assessed by HPLC, UPLC-ESI-QTOF-MS, FT-IR and NMR spectral analysis. The antimicrobial capability of ethyl acetate extract and the purified compound coriloxin was determined by disc diffusion, minimal inhibitory concentration and agar overlay TLC–bioautography assay. The visible LOD of coriloxin antimicrobial activity was found at 10 μg for Escherichia coli and 20 μg for both Staphylococcus aureus and Fusarium oxysporum . Inter- and intra-day precision was determined as the relative standard deviation is less than 6.56%, which proved that this method was precise. The accuracy was expressed as recovery, and the values were found ranging from 91.18 to 108.73% with RSD values 0.94–2.30%, respectively. The overall findings of this investigation suggest that agar overlay TLC–bioautography assay is a suitable and acceptable method for the in situ determination of antimicrobial pharmaceuticals.